Multi-Modal Responses to Literature: A Teacher Educator’s Classroom Inquiry (LEARNing Landscapes, 2011)
Approaches to the effective integration of technology in learning and teaching continue to develop at lightning speed. This ongoing inquiry explores multi-modal literature response as a relevant component of teacher education. Illustrative examples of four multi-modal literature responses created by teacher candidates are embedded as hyperlinks. The author’s work highlights multi-modal expression as an innovative approach to literature response in contemporary classrooms, one way of "bridging" print and digital literacies, and as professional learning for both pre-service and practicing teachers in the "new literacies."
Keywords: technology; education; teacher eductaion; multi-modal; literacy; digital; print; professional learning; new literacy